Where are the drought tolerant crops? An assessment of more than two decades of plant biotechnology effort in crop improvement. (August 2018) - Nuccio, Michael L.; Paul, Matthew; Bate, Nicholas J.; Cohn, Jonathan; Cutler, Sean R.
Highlights: The significant global investment in GM technology to improve plant response to water deficit has produced few products. Significant progress has been made identifying genes that have a positive effect on plant response to water deficit. There is a notable disconnect between simulated water deficit in pots and the impact of water deficit on crop productivity. Field research confines drought tolerance trait evaluation to one season per hemisphere per year, which slows progress. The cost of bringing a GM product to market limits the development of drought tolerance GM traits to large acreage crops. Abstract: Since the dawn of modern biotechnology public and private enterprise have pursued the development of a new breed of drought tolerant crop products. After more than 20 years of research and investment only a few such products have reached the market. This is due to several technical and market constraints. The technical challenges include the difficulty in defining tractable single-gene trait development strategies, the logistics of moving traits from initial to commercial genetic backgrounds, and the disconnect between conditions in farmer's fields and controlled environments. Market constraints include the significant difficulty, and associated costs, in obtaining access to markets around the world. Advances in the biology of plant water management, including response to water deficit reveal new opportunities to improve crop response to water deficit and new genome-based tools promise to usher in the next era of crop improvement. As biotechnology looks to improve crop productivity under drought conditions, the environmental and food security advantages will influence public perception and shift the debate toward benefits rather than risks.